Buddhism in South-East Asia: a cultural survey - Ahir, D. C. (Sri Satguru Publications, 2001)
Contributed articles.
Includes bibliographical references.
Contributed articles.
2
Keywords: Buddhism / Southeast Asia / History.; Southeast Asia / Civilization.